A bagatelização da literatura de Lima Barreto: análise do legado editorial do escritor - Camargo, Áureo Joaquim [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The thesis aims to demonstrate the editorial course of the works of writer Afonso Henriques de Lima Barreto (1881-1922), analyzing the changes and continuities that have taken place in the editorial writer's legacy after his death. We call bagattelization the way the writer joined the texts of Bagatelas, published in 1923, a model that has shaped the posthumous editions organized by Francisco de Assis Barbosa reflected in the publications of other publishers, subsequent to their work. We examine the process of bagatellization of Lima Barreto literature by two biases: a) developed by Lima Barreto, a result of the satirical vein of the writer; and b) the bagatellization performed by Francisco de Assis Barbosa, resulted by the demands inherent in the publishing market, described in its main trends throughout its evolution until almost our time. The conducting wire of the thesis summarized the discussion of bagatellement’s process of Lima Barreto work was distributed by four chapters. At first, we’ll approach the time interval between 1909-1923, when the editorial writer's legacy constitute oneself , composed by the publication of seven works .The second comprehends the interval 1923-1956 , when the editorial writer's legacy is on the one hand , maintained by publishers , and on the other , undergoes changes and expansions, reaching production of the writer a total of ten volumes.The third has the exclusive purpose of trying to treat Francisco de Assis Barbosa to offer in 1956 by Brasilense publisher to market the complete works of Lima Barreto, with limabarretiano legacy reaching seventeen volumes mark.The final chapter presents existing editorial trends in the publications of the works of Lima Barreto post- 1956 marked by two aspects: on the one hand, the continued and uncritical repetition of the texts set in the edition of 1956 by Francisco de Assis Barbosa, almost unique reference; other by the emergence of issues that implicitly dialogue with the edition 1956, aiming to provide the market with different editions of barbosiano standard while retaining, even residually, however, signals bagatellization process.

Esta tese objetiva demonstrar o percurso editorial do escritor carioca Afonso Henriques de Lima Barreto (1881-1922), analisando as modificações e as permanências no legado editorial do escritor após sua morte. Chamamos de bagatelização a maneira como o escritor juntou os textos do livro Bagatelas, publicado em 1923, modelo que plasmou as edições póstumas organizadas por Francisco de Assis Barbosa. Analisamos o processo de bagatelização da literatura de Lima Barreto por dois vieses: a) o desenvolvido por Lima Barreto, resultado da veia satírica do escritor; e b) a bagatelização realizada por Francisco de Assis Barbosa, motivada pelas exigências inerentes do mercado editorial. Assim, há pelos quatro capítulos que compõem a tese o fio condutor da discussão do processo bagatelizador da obra de Lima Barreto, embasado pela descrição da evolução do mercado editorial brasileiro. No primeiro capítulo, tomamos o espaço temporal de 1909 a 1923, momento da constituição do legado editorial do escritor, com sete obras publicadas. O segundo capítulo compreende o intervalo temporal de 1923 a 1956, quando o legado editorial do escritor é, por um lado, mantido pelas editoras, e por outro sofre alterações e ampliações, atingindo um total de dez volumes. O terceiro capítulo tem por objetivo exclusivo a tentativa de se oferecer ao mercado as obras completas de Lima Barreto, executada por Francisco de Assis Barbosa, com o legado editorial limabarretiano atingindo o total de dezessete volumes. O último capítulo apresenta as tendências editoriais existentes nas publicações das obras de Lima Barreto pós-1956 marcadas por dois aspectos: por um lado a repetição continuada e acrítica dos textos fixados na edição de 1956 por Francisco de Assis Barbosa, quase única referência; por outro, pelo aparecimento de edições que dialogam implicitamente com a edição de 1956, visando a oferecer ao mercado edições distintas do padrão barbosiano.
The bagatellization of Lima Barreto's literatura: an analysis of the editorial writer's legacy
Keywords: Works; Editions; Bagatellization; Publishing; Lima Barreto; Obras; Edições; Bagatelização; Mercado editorial